Corporate social responsibility in Singapore : perceptions and practices. - Luo, Wanyin. (2008)
This study explored the perceptions about corporate social responsibility (CSR) among a sample of corporate executives and the CSR practices of a sample of corporations in Singapore. In doing so, the study focused on activities, motivations, decision-making processes, stakeholders, communication processes, resource allocation, evaluation, and benefits of CSR.